2008
DOI: 10.1039/b802946f
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of precious metals by using chemically modified waste paper

Abstract: Waste newsprint paper was chemically modified with p-aminobenzoic acid to prepare a sorption active gel. This gel proved useful for the selective uptake of gold, palladium and platinum over other coexisting metal ions such as copper, nickel, zinc and iron. A remarkably high capacity for Au(III) was observed together with a moderate uptake of Pt(IV) and Pd(IV). Furthermore, Au(III) was reduced to elemental gold which formed aggregates. A high percentage recovery of the precious metal ions (85-95%) and regenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…These results prove that gold particles formed on gel surface by the reduction process exhibit a certain sort of tendency to be detached from the gel surface forming clear aggregates. A similar observation was also found in our previous study (Adhikari et al 2008). …”
Section: Adsorption Isothermssupporting
confidence: 86%
“…These results prove that gold particles formed on gel surface by the reduction process exhibit a certain sort of tendency to be detached from the gel surface forming clear aggregates. A similar observation was also found in our previous study (Adhikari et al 2008). …”
Section: Adsorption Isothermssupporting
confidence: 86%
“…The presence of chloride or nitrate species basically facilitates the formation of palladium-chloride/nitrate anionic complexes and eases the ionic interaction between protonated amine groups present in the adsorbent [14,15]. However, the presence of an excess of such anions reduces the metal recovery because the metalanion complex and the anion itself compete for ionic interaction with the positively charged amine group.…”
Section: Adsorption Behavior Of Modified Cwp For Pd(ii)mentioning
confidence: 98%
“…Persimmon wastes were reported to be utilized for adsorption of heavy metals and precious metals from aqueous systems [15][16][17][18][19][20][21]. Nakajima et al reported that the persimmon tannin gel can adsorb vanadium effectively from aqueous solutions containing VOCl 2 and NH 4 VO 3 [15].…”
Section: Introductionmentioning
confidence: 98%